PERFORMANS BOBOT BADAN AYAM LINGNAN UMUR 8 – 16 MINGGU YANG DIPELIHARA DI MANOKWARI PAPUA BARAT - Lumatauw, Sintje; Iroth, Wandy Joudy; Chotimah, Siti Chusnul (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2010)
A study was initiated to identify body weight performance of Chinese traditional Lingnan chicken at 8 to 16 weeks of age. Both male and female body weight and feed consumption were recorded. Four hundred and sixty eight Lingnan chickens (108 males and 360 females) were randomly distributed to 12 experimental cage unit of 3 x 4 m followed a Completely Randomized Design. The chickens were treated with four different ration combinations which consisted of commercial ration, yellow corn, and rice brand. Each treatment was replicated three times. Result of the study showed that the male Lingnan chicken was heavier than the females at each observation. The different body weight was 335, 498, 557, 637 and 553 grams at the age of 8, 10, 12, 14 and 16 weeks, respectively. At 16 weeks, the male Lingnan average body weight was 2927 grams while the female was 2374 grams. Four different ration combinations were not significantly affected the chicken body weight (P>0.05).